2014
DOI: 10.3906/vet-1404-54
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and hypoxia-inducible factor-1 alpha during the periovulatory period in goats

Abstract: To evaluate the expression of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1 alpha (HIF-1α) during the periovulatory period, goat ovaries were collected at 0, 4, 8, 12, 24, and 48 h after treatment with 300 IU hCG. Total cellular RNA was isolated and VEGF and HIF-1α were quantified using real-time RT-PCR. The mRNA levels of VEGF in thecal tissue remained unchanged prior to ovulation. However, the mRNA levels of VEGF in thecal tissues at 48 h increased to 7.5-fold of the level at 0 h (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, in our study, cows fed the OTM had a greater number of small and large follicles as well as size of large follicles. Greater P4 concentrations have a positive effect on follicular turnover increasing the number of young large follicles with the potential to ovulate and subluteal concentrations extend the growth of follicles (Navanukraw et al, 2014;Thammasiri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our study, cows fed the OTM had a greater number of small and large follicles as well as size of large follicles. Greater P4 concentrations have a positive effect on follicular turnover increasing the number of young large follicles with the potential to ovulate and subluteal concentrations extend the growth of follicles (Navanukraw et al, 2014;Thammasiri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SULT1C3 , a member of sulfotransferase family, catalyzes the sulfate conjugation of several hormones 47 , 48 , and regulates estrogen removal in estrogen metabolic pathway 19 . In addition, HIF1ß is a critical mediator of follicle development and ovulation and a regulator of gene expression in ovary 49 , 50 . Several genes, such as INSL3 , STAR , and HIF1ß , were associated with follicular development, ovulation, and steroid secretion in the ovary of Qira black sheep at estrous and anestrous 37 .…”
Section: Discussionmentioning
confidence: 99%